2021
DOI: 10.3390/s21082690
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Transmit Antenna Subset Selection for Multiuser Space–Time Line Code Systems

Abstract: We consider the problem of the efficient transmit antenna subset (TAS) selection for maximizing the signal-to-interference-plus-noise ratio (SINR) of multiuser space–time line code (MU–STLC) systems [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Our proposed algorithm is also compared with [21,28,29], which are among the simplest and following similar approaches to the best of our knowledge. The complexity order of each is [21] our proposed technique [28,29] and random selection according to ( 27) and (28).…”
Section: Results and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Our proposed algorithm is also compared with [21,28,29], which are among the simplest and following similar approaches to the best of our knowledge. The complexity order of each is [21] our proposed technique [28,29] and random selection according to ( 27) and (28).…”
Section: Results and Analysismentioning
confidence: 99%
“…Our proposed algorithm is also compared with [21,28,29], which are among the simplest and following similar approaches to the best of our knowledge. The complexity order of each is [21] our proposed technique [28,29] and random selection according to ( 27) and (28). We also found that the proposed algorithm is more energy-efficient than random at the cost of some complexity, which is less than that of [21].…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…As summarized in Refs. [ 18 , 19 , 20 ], its applications to various MIMO communication systems have been actively investigated. In particular, we have proposed an STLC-applied NOMA (STLC-NOMA) system for uplink IoT networks while raising some issues about the conventional uplink NOMA systems [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%